Probabilistic Landslide risk assessment - Application to Eastern Rif (Morocco) - Mohamed RFIFI; Lahsen AIT BRAHIM (MATEC Web of Conferences, 2018)
The present study is consecrated to the probabilistic mapping of the landslide risk at the local scale of an area that belongs to Al Hoceima city in the western Rif of Morocco. The study focuses mainly on the spatial analysis of multi sources data by using an environment GIS (Geographic Information Systems), and the application of the bivariate probabilistic model to qualify the risk susceptibility. The employed methodology is based on three stages. First, the evaluation of landslide susceptibility (S) by the analysis model cited before. Second, the identification and the estimation of the potential consequences (C) for the existing issues. Finally, the landslide risk (R) is evaluated by combining the susceptibility and the potential consequences map. This study requires the use of spatial analysis techniques. It also refers to the risk maps scale, generally reduced and being inappropriate at the urban project area. The obtained risk map defines four risk intensities with a spatial resolution of two meters.